Food Adulteration and Bio-Magnification of Environmental Contaminants: A Comprehensive Risk Framework for Bangladesh - Majed, Nehreen; Real, Md. Isreq H.; Akter, Marufa; Azam, Hossain M. (Frontiers in Environmental Science, 2016)
This article thoroughly investigates the severity of the prevailing environmental conditions and evaluates the resulting threats to food intake and public health in Bangladesh by establishing relationship among different contaminant transfer mechanisms to human. It describes the potential of certain contaminants to get bio-magnified through the food chain. A database was prepared on a number of contaminants in the study area that are responsible for rendering different foods vulnerable to produce long term or short-term health effects. Contaminants that have been identified in the food sources were categorized in a continuum based on their allowable daily intake. A protocol has been developed which will enable the assessment of the potential of a contaminant to bio-magnify through food chain to understand the contribution of a contaminant on different levels of food chain. The study also provides a detailed assessment of the public health risks associated with direct ingestion of adulterated foods and intake of contaminants through food chain or water intake. Their intake to human body was quantified, which provides an indication of the toxicity level of the contaminants and possible impact on human health. The traditional four steps of risk assessment technique have been employed for some model contaminants (including metals, organic contaminants and food adulterants). Additionally, existing rules and regulations of Bangladesh were identified with possible limitations that can play significant role in controlling the food adulteration practices and concentration of contaminants in the environment and human body. Finally, a holistic approach to necessary interventions has been prescribed at policy, treatment and evaluation level to prevent the water pollution and food adulteration. Thus, a much-needed comprehensive framework is prescribed in this study to promote safety in food handling, preserve environment and improve health-based strategies in Bangladesh.